The effect of tax amnesty and taxpayer awareness to taxpayer compliance with financial condition as intervening variable - Lisa, Oyong; Hermanto, Bambang (International Research Journal of Management, IT & Social Sciences, 2018)
This study aimed to analyze the influence Tax Amnesties and awareness of taxpayer on the financial condition and taxpayer compliance, analyze the influence of financial condition on tax compliance and to analyze the influence of Tax Amnesties and awareness of taxpayers on tax compliance with financial conditions as moderating. Analysis using techniques Structural Equation Modeling (SEM). The result showed that Tax Amnesties and awareness of taxpayer have a significant effect on financial condition and taxpayer compliance. Then, the financial condition has a significant effect on tax compliance. The result also showed that Financial Condition is mediating the effect of Tax amnesties and tax payerâs awareness of tax compliance. The financial condition strengthens the relationship between the Tax amnesties and awareness of taxpayers with tax compliance in paying taxes. If the taxpayer has the willingness to pay tax, compliance in paying taxes will be high when supported with tax payers financial condition.